2008
DOI: 10.1186/1471-2288-8-47
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of two frequently used self-administered physical activity questionnaires in adolescents

Abstract: Background: To create and find accurate and reliable instruments for the measurement of physical activity has been a challenge in epidemiological studies. We investigated the reliability and validity of two different physical activity questionnaires in 71 adolescents aged 13-18 years; the WHO, Health Behaviour in Schoolchildren (HBSC) questionnaire, and the International Physical Activity Questionnaire (IPAQ, short version).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
156
1
16

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(192 citation statements)
references
References 42 publications
15
156
1
16
Order By: Relevance
“…Over the recent years, the issue of physical activity among school learners has also been addressed more frequently by Polish researchers [16][17][18][19][20][21], who have shown that physical activity of young people in Poland is not sufficient. Those findings are consistent with the reports on the unsatisfying level of physical activity of young people in some other countries [22][23][24][25][26].…”
Section: Introductionsupporting
confidence: 93%
“…Over the recent years, the issue of physical activity among school learners has also been addressed more frequently by Polish researchers [16][17][18][19][20][21], who have shown that physical activity of young people in Poland is not sufficient. Those findings are consistent with the reports on the unsatisfying level of physical activity of young people in some other countries [22][23][24][25][26].…”
Section: Introductionsupporting
confidence: 93%
“…Most of the questions were also used in WHO's Health Behavior in School-aged Children study with 11-15-year-old children (Currie et al, 2001), but to our knowledge the questions have not been validated in this age group. However, the questions on physical activity have been validated among 13-18-year old adolescents (Rangul et al, 2008), showing that these questions had good validity. In our view, it would have been problematic to use parents' reports on their child's health behavior, because parents do not automatically know about their child's food intake, TV viewing, computer use or physical activity that well.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the responses were all voluntary so there is no reason to believe there was any bias particularly as the objectives were pure research rather than attached to any vested interest situations. Various studies, for example, Rangul et al (2008), have shown self-reporting is relatively accurate. Anonymity was guaranteed and the questionnaire vetted by the Lincoln University social science human ethics committee.…”
Section: Methods: Information Gathering and Analysismentioning
confidence: 99%